2011
DOI: 10.1007/s10554-011-9894-2
|View full text |Cite
|
Sign up to set email alerts
|

Automatic centerline extraction of coronary arteries in coronary computed tomographic angiography

Abstract: Coronary computed tomographic angiography (CCTA) is a non-invasive imaging modality for the visualization of the heart and coronary arteries. To fully exploit the potential of the CCTA datasets and apply it in clinical practice, an automated coronary artery extraction approach is needed. The purpose of this paper is to present and validate a fully automatic centerline extraction algorithm for coronary arteries in CCTA images. The algorithm is based on an improved version of Frangi’s vesselness filter which rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 23 publications
0
137
0
Order By: Relevance
“…There was no significant exclusive of focal stenosis. Segmentation was performed according to AHA nomenclature (17). Segments with image artifact, stents, bypass vessels, or clips were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant exclusive of focal stenosis. Segmentation was performed according to AHA nomenclature (17). Segments with image artifact, stents, bypass vessels, or clips were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, the filter may also produce high values near large bright structures like aorta. Authors of [27] proposed the modified vesselness function; however, we observed false filter response only near the aorta, and, thus, we propose an alternative approach for segmentation correction only near the aorta border. It should be noted that conventional remove-islands procedure may not eliminate the segmentation errors since false regions are attached to the arteries.…”
Section: Vessel Segmentationmentioning
confidence: 82%
“…In the current work, we extend this algorithm to cerebral datasets. Pulmonary arteries are removed by the morphological operations proposed in [27]. Bone elimination is an essential step for cerebral artery segmentation due to vertebral arteries and cervical vertebrae proximity.…”
Section: Vessel Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [83] described successful validation of a fully automatic centerline extraction algorithm for coronary arteries in CTA images.…”
Section: Computed Tomographymentioning
confidence: 99%